1989
DOI: 10.1126/science.2474200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Apical Chloride Channels in the Gastric Oxyntic Cell

Abstract: Oxyntic cells that retain distinct morphological polarity between apical and basolateral membranes were isolated from the gastric mucosa of the amphibian Necturus. Patch-clamp techniques were applied to these cells to identify apical membrane ion channels associated with hydrochloric acid secretion. A single class of voltage-dependent, inwardly rectifying chloride channels was observed in the apical membranes of both resting and stimulated (acid-secreting) oxyntic cells. Stimulation of the cells with dibutyryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 18 publications
(18 reference statements)
0
17
1
Order By: Relevance
“…In resting cells that have been incubated in Cl-free solutions and then exposed again to Cl, the rate at which Cl enters the cells (71 mM/min) was approximately equal to the rate of HCO3 loss (measured from the rate of pHi decrease during the initial stages of Cl treatment, calculated to be 81 mM/ min). In the histamine-stimulated cells, when it is expected that the Cl channels in the apical membrane have been activated (Demarest et al, 1989), there was still good agreement between the Cl fluxes (70 mM/min) and the HCO3 fluxes (77 mM/min). In addition, it has been shown previously that 200-500 ,uM H2DIDS largely blocks the Cl-induced changes of pHi (Paradiso et al, 1987), and the present experiments have shown that Cl fluxes were blocked by -80% (Figure 9).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In resting cells that have been incubated in Cl-free solutions and then exposed again to Cl, the rate at which Cl enters the cells (71 mM/min) was approximately equal to the rate of HCO3 loss (measured from the rate of pHi decrease during the initial stages of Cl treatment, calculated to be 81 mM/ min). In the histamine-stimulated cells, when it is expected that the Cl channels in the apical membrane have been activated (Demarest et al, 1989), there was still good agreement between the Cl fluxes (70 mM/min) and the HCO3 fluxes (77 mM/min). In addition, it has been shown previously that 200-500 ,uM H2DIDS largely blocks the Cl-induced changes of pHi (Paradiso et al, 1987), and the present experiments have shown that Cl fluxes were blocked by -80% (Figure 9).…”
Section: Discussionmentioning
confidence: 90%
“…Under these conditions, there will be an inward movement of Cl in exchange for intracellular HCO3. The decrease in Cli compared with the resting cell is likely to be due to the opening of Cl channels in the apical membrane (Demarest et at., 1989), because the decrease of Cli noted during histamine stimulation was not affected by the anion exchanger inhibitor H2DIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cyclic AMP-stimulated Cl-channels (12 pS of unit conductance) were found in the apical membrane region of isolated Necturus oxyntic cells (Demarest, Loo & Sachs, 1989). The contribution of this type of Cl-channel to the present wholecell Cl-current can be ruled out; because (1) the power spectra of the Cl-current had only one corner frequency (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the parietal cells have been shown to secrete HCl with a pH of 0.8 (Demarest et al, 1989). In freshwater rainbow trout (Bucking and Wood, 2009) and seawater steelhead trout (C.B.…”
Section: Introductionmentioning
confidence: 99%